Mineralogy and Geochemistry of Pyrite and Arsenopyrite from the Zaozigou Gold Deposit in West Qinling Orogenic Belt, Central China: Implications for Ore Genesis. Issue 3 (16th April 2019) - Tang, Qingyan; Di, Pengfei; Yu, Man; Bao, Jian; Zhao, Ying; Liu, Dongxiao; Wang, Yuxi
Abstract: The Zaozigou gold deposit lies in the West Qinling orogenic belt, Gansu Province, China. It is one of the largest gold deposits, and the orebodies are hosted in fine‐grained slates intercalated with limestone of the Middle‐Triassic Gulangdi Formation and varied dykes. The gold orebodies are strictly controlled by the NE‐, NW‐, and SN‐trending tensional and shearing faults with high dipping angle. The mineralogy and geochemistry of pyrite and arsenopyrite are measured by electron microprobe. Pyrite has up to 0.12 wt.% Au, and arsenopyrite contains up to 0.17 wt.% Au. The antithetic correlation between S and As indicates the substitution of As for S in pyrite, and arsenic occurs in anionic As 1− state in the pyrite structure under the reduced conditions. Pyrite has relatively high Co ( 364–2248 ppm) but relatively low Ni ( 109–497 ppm) contents, with Co/Ni ratios ranging from 1.63 to 10.50, indicating that the deposit originated from a volcanogenic fluid and remobilized by hydrothermal fluid. Au in arsenopyrite occurs as cationic Au in solid solution, whereas Au in pyrite is in solid solution and metal nanoparticles (Au 0 ). The texture characteristics and trace element geochemistry among cores, transition zones, and rims of pyrites demonstrate that there are at least four pulses of fluid participating in the generation of pyrite in the deposit. The calculated formation temperatures of the Zaozigou deposit vary from 148°C to 304°C, with an average temperature of 213°C based on Au contents in pyrite. The Pb isotopic compositions of pyrite samples suggest that the metallogenic materials of the Zaozigou deposit were derived from the mantle and upper crust. All the characteristics above lead us to draw the conclusion that the Zaozigou gold deposit is classified as an epithermal deposit. Abstract : The Zaozigou gold deposit in West Qinling has multiple pulses of fluid participating in the generation of pyrite. The metallogenic materials of this deposit are derived from the mantle and upper crust. The Zaozigou gold deposit may be classified as an epithermal deposit.